Cross-Border Data Security: Analysis of High-Profile Violations and Mitigation Strategies - Riska Nofharina Lutfiah; Tunjung Sulaksono (Faculty of Computer Science Universitas Indonesia, 2025)
The increase in cross-border data transfers has resulted in a surge in data breaches in various jurisdictions. This study seeks to examine the pattern of data breaches in notable incidents, including Facebook (2019), SolarWinds (2020), Tokopedia (2020), and LinkedIn (2021). This research uses a qualitative case study methodology to assess prominent vulnerabilities in data security systems and look at recurring patterns based on the CIA TRIAD (Confidentiality, Integrity, Availability) theoretical framework. The findings show that the main weaknesses in data breaches are inadequate encryption, weak software supply chain security, and inadequate API protection. This paper recommends mitigation techniques based on the findings, which include improving encryption, integrating blockchain into the software supply chain, strengthening API authentication, and using artificial intelligence (AI) to identify cyber threats and contributes to improving the understanding of regulations such as GDPR, PIPL (China), and PDP laws (Indonesia) in mitigating the dangers of global data breaches.